A new species of Colostethus (Anura, Dendrobatidae) from French Guiana with a redescription of Colostethus beebei (Noble, 1923) from its type locality - Kok, Philippe J. R.; MacCulloch, Ross D.; Gaucher, Philippe; Poelman, Erik H.; Bourne, Godfrey R.; Lathrop, Amy; Lenglet, Georges L. (Phyllomedusa: Journal of Herpetology, 2006)
A new species of Colostethus, long mistaken for Colostethus beebei, is described from French Guiana. The new species can be distinguished from congeners by absence of median lingual process, first finger longer than second, third finger not distinctly swollen in males, differences in tadpole morphology, coloration and pattern (e.g. absence of dorsolateral stripe), bioacoustics, and reproductive behavior. A complete redescription of Colostethus beebei plus description of its tadpole and call is provided on the basis of recently collected topotypic specimens. The range of C. beebei is restricted to the Kaieteur plateau, Pakaraima Mountains, Guyana.